Bad play: real-world issues for players who are involved with inappropriate boundary-crossing behaviors in virtual world - Yu, Qinshu (Nanyang Technological University, 2025)
This study investigated changes in players' personal boundary adjustments encompassing physical, emotional and physiological boundaries in virtual worlds. Personal boundaries (or so-called psychological boundary) are defined as rules distinguishing what is allowed and not allowed within a person's region. These boundaries exist within relationships, are dynamic and adjustable, and serve as markers differentiating "self" from "non-self." Violating boundaries implies a negation of personal "identity" and "existence," leading to discomfort and offense. In the virtual reality (VR) world, the Proteus effect—the phenomenon where player behavior is influenced by virtual avatars and world virtualization—may cause behavior differences from the real world. Virtual avatars are digital representations of players within the VR environment. The establishment of personal boundaries might be affected by these influenced behaviors. To explore the impact of world virtualization on players' boundary adjustments and the resulting differences in their perceptions and behaviors compared to the real world, the project conducted a two-part qualitative experiment. The first experiment invited participants to enter a VR scene where non-player characters (NPCs) engaged in conversations that challenged their boundaries within the virtual environment. After the VR session, players participated in interviews to freely express their feelings, thoughts, expectations, and desired responses to having their boundaries violated in the virtual world. They also compared the actions they intended to take in VR with those they would take in the real world. The study expected that players might adjust their personal boundaries in the virtual world, resulting in behavioral and attitudinal differences when offended compared to the real world. Identifying the specific aspects in which these differences occurred was the qualitative exploration objective of the project. This research aimed to deepen the understanding of how virtualization influences personal boundary dynamics and the broader implications for player interactions and experiences in virtual environments.